Analyzing a successful journey of building engaged online communities through social media: The optimal innovation of customer loyalty programs. Issue 1 (13th January 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: This case study paper concentrates on the capacity of innovative applications of social media-led communication to inject added value into customer loyalty programs, based upon an analysis of the highly successful Shop Your Way (SYW) program run by Sears in the USA. The results revealed that social media is a pivotal force in the pursuit and retention of loyal customers, since individuals respond positively to participating in an ongoing experience of collecting rewards distributed on social platforms. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.